A Conserved Role for Asrij/OCIAD1 in Progenitor Differentiation and Lineage Specification Through Functional Interaction With the Regulators of Mitochondrial Dynamics - Ray, Arindam; Kamat, Kajal; Inamdar, Maneesha S. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are highly dynamic organelles whose activity is an important determinant of blood stem and progenitor cell state. Mitochondrial morphology is maintained by continuous fission and fusion and affects stem cell proliferation, differentiation and aging. However, the mechanism by which mitochondrial morphology and dynamics regulate cell differentiation and lineage choice remains incompletely understood. Asrij/OCIAD1 is a conserved protein that governs mitochondrial morphology, energy metabolism and human embryonic stem cell (hESC) differentiation. To investigate the in vivo relevance of these properties, we compared hESC phenotypes with those of Drosophila hematopoiesis, where Asrij is shown to regulate blood progenitor maintenance by conserved mechanisms. In concordance with hESC studies, we found that Drosophila Asrij also localizes to mitochondria of larval blood cells and its depletion from progenitors results in elongated mitochondria. Live imaging of asrij knockdown hemocytes and of OCIAD1 knockout hESCs showed reduced mitochondrial dynamics. Since key regulators of mitochondrial dynamics actively regulate mitochondrial morphology, we hypothesized that mitochondrial fission and fusion may control progenitor maintenance or differentiation in an Asrij-dependent manner. Knockdown of the fission regulator Drp1 in Drosophila lymph gland progenitors specifically suppressed crystal cell differentiation whereas depletion of the fusion regulator Marf (Drosophila Mitofusin) increased the same with concomitant upregulation of Notch signaling. These phenotypes were stronger in anterior progenitors and were exacerbated by Asrij depletion. Asrij is known to suppress Notch signaling and crystal cell differentiation. Our analysis reveals that synergistic interactions of Asrij with Drp1 and Marf have distinct impacts on lymph gland progenitor mitochondrial dynamics and crystal cell differentiation. Taken together, using invertebrate and mammalian model systems we demonstrate a conserved role for Asrij/OCIAD1 in linking mitochondrial dynamics and progenitor differentiation. Our study sets the stage for deciphering how regulators of mitochondrial dynamics may contribute to functional heterogeneity and lineage choice in vertebrate blood progenitors.